MEDIASI LINGKUNGAN KERJA PADA PENGARUH KOMPETENSI TERHADAP KINERJA PEMBATIK DI ERA REVOLUSI INDUSTRI 4.0 - Susi Widjajani; Fitri Rahmawati (FE Program Studi Manajemen, 2020)
This study aims to examine the role of mediation in the work environment on the effect of competence on performance. The population of this study were all UMKM batik makers in Lendah, Kulon Progo Regency with a total of 60 people. The sampling technique uses census techniques where all members of the population are sampled. Data analysis was performed using Hierarchical Regression Analysis. The research instrument used in this study was a questionnaire, which was adopted from several previous studies and had tested its validity and reliability. The results show that the competency variable has a significant positive effect on performance and work environment, the work environment has a significant positive effect on performance, and the work environment partially mediates on the effect of competence on performance.Key word: Competence, Performance, Work Environment